Effect of morning vs evening feeding of limit-fed Holsteins during summer months - Brandt, Robert T., Jr.; Reinhardt, Christopher D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Thirty-eight Holstein steers (avg 339 lb) were grouped into four weight blocks, with two pens per block. Within each block, cattle in one pen were fed at 8:00 a.m. and those in the other at 8:00 p.m. All cattle were limit-fed to achieve a programmed rat e of gain of 2.2 lbs/d using NRC net energy equations. The trial lasted from July 13 through September 6, 1993. With the same quantity of feed, cattle fed in the evening gained 18% faster than cattle fed in the morning (P<.02) resulting in better feed efficiency for the evening-fed cattle (P<.06). Average high temperature for the 56-day period was 88F, average low temperature was 69 ̊F, average relative humidity was 73%, and average wind speed was 1.8 mph. Feed tended to be consumed within a 3-hour period, regardless of time of feeding. Because the effective ambient temperature frequently rose above the upper critical temperature for cattle (77 ̊F), animals needed to expend energy to dissipate excess heat. These results indicate that cattle limit-fed during the summer may utilize metabolizable energy more efficiently if allowed to ferment the bulk of their feed during the cooler hours of the evening.
Keywords: Beef; Limit-feeding; Heat stress; Night feeding